2002
DOI: 10.1292/jvms.64.83
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Estrus during the Non-Breeding Season in Egyptian Baladi Goats.

Abstract: ABSTRACT. The induction of estrus during the non-breeding season was investigated in 100 Egyptian Baladi goats (Capra hircus). All animals assigned to treatments had low progesterone concentrations (<0.5 ng/ml) tested 2 times 10 days apart to confirm anestrous condition. Animals were assigned to three experimental groups. A group of animals received subcutaneous norgestomet ear implant for 11 days and a single i.m injection of PGF2α 24 hr before implant removal (group I; n=40). Second group of animals received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
4
5
1
Order By: Relevance
“…On the other hand, Reyna et al 33 reported that oestrous synchronization in sheep by means of intravaginal sponge treatment (30 mg, FGA) for 12 days in the non-breeding season associated with the administration of 400 IU of PMSG and finally, 40 mcg of GnRH 36 h after sponge withdrawal, yielded similar pregnancy rates in the animals administered with GnRH (23%) and those maintained as controls (21%). The findings obtained in the present study for the effects of the combination of GnRH administration at TAI on pregnancy rates in goats were in agreement with the findings obtained by Reyna et al 33 in sheep, but were different from the findings reported by Medan et al 32 in goats. The difference may have arisen from the type of progestagen used, the timing of GnRH administration and the GnRH dose administered and the hormonal status occurring in the transition period.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…On the other hand, Reyna et al 33 reported that oestrous synchronization in sheep by means of intravaginal sponge treatment (30 mg, FGA) for 12 days in the non-breeding season associated with the administration of 400 IU of PMSG and finally, 40 mcg of GnRH 36 h after sponge withdrawal, yielded similar pregnancy rates in the animals administered with GnRH (23%) and those maintained as controls (21%). The findings obtained in the present study for the effects of the combination of GnRH administration at TAI on pregnancy rates in goats were in agreement with the findings obtained by Reyna et al 33 in sheep, but were different from the findings reported by Medan et al 32 in goats. The difference may have arisen from the type of progestagen used, the timing of GnRH administration and the GnRH dose administered and the hormonal status occurring in the transition period.…”
Section: Discussionsupporting
confidence: 69%
“…In sheeps the GnRH administrations 24-44 h after the progestagen treatment synchronized estrous but did not increase the fertility 18,19 . Medan et al 32 reported that in which implants containing norgestomet were placed into the ear of goats for 11 days in the non-breeding season and the animals were administered with 125 mg of cloprostenol 24 h prior to implant removal with one group having been administered with 10.5 mcg of GnRH 24 h after implant removal, the pregnancy rates in the group administered with GnRH and the group that did not receive GnRH as 70% and 57.5%, respectively. On the other hand, Reyna et al 33 reported that oestrous synchronization in sheep by means of intravaginal sponge treatment (30 mg, FGA) for 12 days in the non-breeding season associated with the administration of 400 IU of PMSG and finally, 40 mcg of GnRH 36 h after sponge withdrawal, yielded similar pregnancy rates in the animals administered with GnRH (23%) and those maintained as controls (21%).…”
Section: Discussionmentioning
confidence: 99%
“…Cyprus goats were introduced in Iraq and it's known as Damascus goat or Shami goats have some advantages Fertility, prolificacy as averaging 1.80 kids per doe kidding and dual purpose animal (meat and milk), however, it is considered a seasonal breeder which it starts in late August and extends through mid-December (Mavrogenis et al, 2006).The reproductive seasonality impact of variation on the price of meat and milk over the year, which affects the economy of farmers and the food industry (Gómez-Brunet et al, 2012).To solve this problem, researchers and breeders used tools to develop relevant techniques to manipulate the sexual activity of animals (Delgadillo, 2011). There are many methods for manipulation of reproduction, one method by using hormonal of these treatments (Medan et al, 2002; body of evidence that this neuropeptide regulates seasonal reproduction (Revel et al, 2006;Clarke et al, 2009). The seasonal change in Kiss1 expression, the extent to which kisspeptin cells provide input to the GnRH neurons is greater during the breeding season than in the non-breeding season (Smith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gonadotropin releasing hormone (GnRH) or human chorionic gonadotropin (hCG) injections are applied to improve the reproductive performance in anestrus goats (Medan et al, 2002;Rodríguez-Martínez et al, 2018). A strategy of reproductive performance included inducing estrus and ovulation (Cameron et al, 1988;Khan et al, 2003;González-Álvarez et al 2016).The hCG has an activity similar to luteinizing hormone (LH), while the GnRH acts on the pituitary gland, stimulates the release of LH and FSH and subsequently the secretion of steroid hormones from the gonads.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible to obtain successful pregnancy using intravaginal sponges or subcutaneous norgestomet ear implants in seasonally anoestrus goats 6 . Apparently, they could be used alone, but some administrations were supplemented with PGF 2 α and eCG for a superior outcome [7][8][9][10][11] . The eCG alone was reported to be inadequate to ensure satisfactory synchrony in deep anoestrous 12 .…”
Section: Introductionmentioning
confidence: 99%